SUBSTANSI IBADAH YANG MURNI DAN APLIKASINYA DALAM IBADAH GEREJA MASA KINI, KAJIAN SURAT YAKOBUS 1:26-27 - Kris Banarto; Hery Budi Yosef (CV. Denasya Smart Publisher, 2024)
The burden of life that is not light, especially faced by congregations in big cities, causes them to need a balance that can reduce the burden. Instead of looking for God who is the source of peace and happiness. They look for other things that can provide pleasure. The church can provide solutions to people who are heavily burdened, the church needs to find an interesting worship procedure for the congregation without reducing the substance of the worship. The church provides biblical teachings that can change the character of the congregation and grow the faith of the congregation, not just focusing on increasing the number of congregations. The purpose of this study is to determine the meaning of true worship based on the Letter of James 1:26-27 which is applied to the congregation today, especially in big cities. This research method uses qualitative research through literature studies by exegesis of texts, book expositions, and interpretations from theologians supported by the opinions of pastors, religious teachers, congregational councils, and servants of God with open questions. The results of this study are the common thread of understanding worship between worship in the Old Testament, the New Testament, and theologians' translations, so that there is no conflict, but complement each other to become a comprehensive understanding of worship. The conclusion of this study is that pure worship in the Letter of James 1:26-27 is an act of love (threskeia) which is one of the four components of worship in the Bible. The four components in question are service in carrying out worship in the church (leitourgeo), presenting the body (lathreia) as a living, carrying out acts of love (threskeia) such as visiting orphans, and worshiping God in Spirit and truth (proskuneo). While the target or purpose of worship is piety (eusebeia) which is ready to welcome the coming of the Lord. The practice of worship in churches today, especially in big cities, has not focused on acts of love as called for in the Letter of James.